Pengaruh Proteksi Sumber Daya Manusia Dan Kecerdasan Emosional Terhadap Kinerja Pegawai PDAM Kota Makassar - Khaeriyah, Hidayatul; Dahliah, Dahliah; Amir, Amir; Mahmud, Amir (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to analyze the effect of human resources protection and Emotional Intelligence on employee’s  performance in PDAM Kota Makassar. This research uses primary data by conducting direct research in the court by gave questionnaires to 91 respondents. The data analyzed technique was carried out multiple linear regression.           The result of this study partially shows human resources protection has a positive and significant effect on employee’s performance and emotional intelligence has a positive and significant effect on employee’s performance Keywords: Effect of Human Resources Protection, Emotional Intelligence, Employee’s Performance